Thailand : Staff Report for the 2015 Article IV Consultation. - International Monetary Fund. Asia and Pacific Dept. (Washington, D.C. : International Monetary Fund, 2015)
This 2015 Article IV Consultation highlights that after a sharp contraction in the first quarter of 2014, Thailand's economy experienced a modest recovery in subsequent quarters, to expand by 0.7 percent in the year as a whole. Inflation decelerated toward the end of 2014 and became negative in January 2015 owing to a sharp decline in oil prices. The recovery is expected to continue in 2015 with growth projected at 3.7 percent on account of some rebound in consumption, including from lower fuel prices, and in private investment as backlogs of project approvals have been largely cleared by various government agencies.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet